Proteoma quantitativo para identificação de potenciais fatores de virulência em Leishmania infantum - Luiz Carlos Fialho Júnior (2017)
Leishmania infantum is the protozoan responsible for Visceral Leishmaniasis in Americas and Europe, a serious disease that can be fatal if untreated. Human cases range from subclinical infection, with an undetermined number of asymptomatic in endemic areas, to a growing and highly lethal in children. In infected dogs, less than 50% have clinical signs of the disease, however, some succumb within a few months after infection. This clinical signs diversity in humans and canines suggests that both host and parasite factors may be involved in disease variability. Thus, due to its importance and clinical-epidemiological diversity in our country, the study of virulence factors in L. infantum is very promising for the understanding of the parasite-host relationship. In a previous study the virulence of two strains (BH46 and BH400) of L. infantum was characterized, and a higher virulence and infectivity of strain BH400 was observed. In addition, through proteomic analysis of the promastigote form, a total of 63 spots were identified corresponding to 36 proteins of which 16 had previously been associated with the virulence of Leishmania spp. Continuing this line of research, in the present study we included the axenic and splenic amastigote forms of both strains with the objective of comparing the differential abundance of proteins between strains BH46 and BH400. Two quantitative proteomics techniques were used: fluorescent labeling (DIGE) and isobaric labeling (TMT) followed by identification by mass spectrometer. A total of 414 unique proteins that showed differences on abundance were identified, being 68.4% found in the TMT technique, 19.1% in DIGE and 12.6% in both techniques. In Promastigote form, a total of 270 proteins with a difference of abundance between the strains were observed. We also found 302 and 293 differential abundant proteins among the strains in the Axenic Amastigote and in the Splenic Amastigote, respectively. In the BH400 strain, 117 proteins with increased abundance were observed in Splenic Amastigote, while 79 proteins showed decrease. On the other hand, in Axenic Amastigote was observed a greater amount of proteins with abundance diminished (178) while 66 proteins presented increase of abundance. In Promastigote of BH400 the amount of proteins with increased (114) and decreased (115) abundance was similar. The interaction prediction of the proteins identified in each form, demonstrate translation-related proteins and response to oxidative stress-related proteins, as important networks. Among all proteins with a difference of abundance, it was observed that in Axenic Amastigotes form, none biological process was enriched, but simultaneously in the Promastigota and Splenic Amastigote forms of BH400 strain (more virulent) were enriched the metabolic processes: Cellular, Carboxylic Acid, of Organic Substance, and Response to Stress. Furthemore, in the promastigote form of BH400, the Primary Metabolic and Cell Biosynthesis Processes were also enriched. On the other hand, in promastigotes and splenic amastigotes forms of the BH46 strain, the enrichment of the biosynthesis process of nitrogenous compounds was observed, whereas in amastigote forms, the cellular biosynthesis process, gene expression and translation were enriched. It was observed that 14 proteins were simultaneously increased in at least two evolutionary forms of BH400 strain, 8 in promastigote and splenic amastigote, 5 in promastigotes and axenic amastigotes and 1 in amastigotes (axenic and splenic) forms. Also, 20 proteins were simultaneously decreased in two evolutive forms of BH400, 6 of them in promastigote and splenic amastigote, 2 in axenic amastigote and promastigote and 12 in both amastigote forms (axenic and splenic). Finally, a greater similarity between the abundance of the proteins in Promastigote and Axenic Amastigote was observed than in Splenic Amastigote, independently of the strain. The results obtained contribute to the advances in the knowledge of the biology of L. infantum, and many of the identified proteins are promising for a better understanding of the parasite-host relationship in this species, especially in virulence factors study.